L’immaginario storico promosso dai videogiochi: un’opportunità in chiave didattica - Elia, Domenico Francesco Antonio (Studi sulla Formazione/Open Journal of Education, 2024)
The paper aims at discussing how historical knowledge is transmitted in the videogame series “Age of Empires”. Charsky&Mims (2008) suggested that students, at the end of the videogame activity, compare the information gathered with that provided by historical accounts to discover hidden game mechanics. The author argues that, in a perspective of history education through game-based learning (Delgado-Algarra 2020) “Age of Empires” enables the gamer to discover the past in a relatively short time, moving around easily (Brusa, 2022, 75).